2019
DOI: 10.1080/09658211.2019.1652654
|View full text |Cite
|
Sign up to set email alerts
|

Reports of recovered memories of childhood abuse in therapy in France

Abstract: Recovered memories of abuse in therapy are especially controversial if the clients were not aware they were abused before therapy. In the past, such memory recovery has led to legal action, as well as a debate about whether such memories might be repressed, forgotten, or false memories. More than two decades after the height of the controversy, it is unclear to what degree such memories are still recovered today, and to what extent it occurs in France.In our French survey of 1312 participants (M age = 33; 53% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 87 publications
4
23
0
1
Order By: Relevance
“…In keeping with previous research in France, a majority of those reported recovered memories were of sexual abuse (Dodier, Patihis et al, 2019). Also consistent with past research in both the U.S. and…”
Section: Reports Of Recovered Memoriessupporting
confidence: 90%
See 1 more Smart Citation
“…In keeping with previous research in France, a majority of those reported recovered memories were of sexual abuse (Dodier, Patihis et al, 2019). Also consistent with past research in both the U.S. and…”
Section: Reports Of Recovered Memoriessupporting
confidence: 90%
“…In other words, the rate of reported recovered memories might be overestimated due to difficulties in accurately self-assessing in retrospect whether there was a period of time when they could not remember. To address this limit, Dodier, Patihis et al (2019) and Patihis and Pendergrast (2019) asked specifically about recovered memories of child abuse that were unknown to the person before their recall in therapy. In Briere and Conte (1993) Epstein & Bottoms, 2002, who found that 53% of the participants who reported forgetting abuse memories endorsed this explanation).…”
Section: Such a Question Does Not Identify Possible Alternative Mechamentioning
confidence: 99%
“…The current omission in psychology curricula to educate students about repressed memory has important implications for educational policy: psychology students in general, but certainly those who might become therapists later on in their careers, should be educated about the current state of knowledge about repressed memories and ideally at multiple stages during their psychology studies. Such education can help prevent victimisation of both patients and those wrongfully accused of abuse as a result of recovering repressed memories in therapy (e.g., Dodier et al, 2019;Loftus, 2005;Loftus & Davis, 2006;McNally, 2005;Patihis & Pendergrast, 2019). To ensure the long-term effectiveness of such interventions, it is important to take into account rebound effects, the phenomenon that people initially adapt to the new information, but later fall back to their initial views (Thorson, 2016;Walter & Tukachinsky, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This is problematic, because believing in the existence of repressed memories can motivate therapists to engage in suggestive techniques in a well-meant attempt to recover such memories in their patients (cf. Dodier et al, 2019;Patihis & Pendergrast, 2019). Recovering memories of criminal acts that never occurred has serious real life consequences for the accused and their family members.…”
Section: The Current Studymentioning
confidence: 99%
“…of their clients (Dodier et al, 2019;Patihis & Pendergrast, 2019). The data, including those produced by skeptics themselves, show that recovered memories of traumatic events continue to be observed inside and outside clinical settings and involve a variety of events, and occur in a variety of different contexts.…”
Section: Conclusion: the Downside Of Attacking Repressionmentioning
confidence: 97%